Differential activation of Extracellular signal-Regulated Kinase 1 and a related complex in neuronal nuclei - Lundquist, Joseph J. (2008)
The Extracellular signal-Regulated Kinases 1 and 2 (ERKs 1/2) are known to participate in regulating transcription in response to moderate depolarization (synaptic stimulation), but how the same active enzyme can differentially regulate distinct transcriptional programs induced with abnormal depolarization (high potassium) is unknown. We hypothesized that ERK1 or 2 accomplishes this differential nuclear response through close association with other proteins in stable complexes. In support of this hypothesis, we have found that immunoreactivity for an apparent high molecular weight phospho-ERK1-containing complex increased in response to synaptic stimulation, but decreased in response to high potassium; p-ERK immunoreactivity at 44/42 kDa increased in both cases. Evidence supporting the conclusion that the band of interest contained ERK1 in a complex, as opposed to it being an unrelated protein crossreacting with antibodies against p-ERK, is that ERK1 (p44 MAPK) and 14-3-3 were electro-eluted from the 160 kDa band cut from a gel. We also found the nuclear complexes to be exceptionally durable, suggesting a role for the crosslinking enzyme, transglutaminase, in its stabilization. In addition, we found other components of the ERK pathway, including MEK, ERK2, p90RSK, and Elk-1, migrating at higher-than-expected weights in brain nuclei. These results describe a novel stable complex of ERK1 in neuronal nuclei that responds differentially to synaptic and depolarizing stimulation, and thus may be capable of mediating gene transcription in a way distinct from the monomeric protein.